Carbazole‐Fused Polycyclic Aromatics Enabled by Regioselective Scholl Reactions. (4th October 2021) - Zhao, Mengna; Pun, Sai Ho; Gong, Qi; Miao, Qian
Abstract: The synthesis of new carbazole‐fused polycyclic aromatics with interesting geometry and useful properties was explored using Scholl reactions. As found from the Scholl reactions of substrates having two carbazole units linked at different positions through o ‐phenylene, oxidative coupling of carbazole units occurred in a regioselective manner with new carbon–carbon bonds preferably formed at C3 and C4 in N‐alkyl carbazoles. A new N‐containing aromatic bowl was characterized by single‐crystal X‐ray crystallography, and new p‐type organic semiconductors exhibited field effect mobility of up to 0.070 cm 2  V −1  s −1 in solution‐processed thin‐film transistors. Abstract : Carbazole‐fused polycyclic aromatic compounds with interesting geometry and useful properties (see picture) were synthesized by Scholl reactions, which enabled oxidative coupling of carbazole units in a regioselective manner. A nitrogen‐containing aromatic bowl was characterized by X‐ray crystallography, and new p‐type organic semiconductors exhibited field effect mobility of up to 0.070 cm 2  V −1  s −1 in solution‐processed thin‐film transistors.